Insights for establishing uric acid reference values in the pediatric population (Research, Society and Development, 2023)
Introduction: Nephrolithiasis is a disease that affects the renal system, characterized by the accumulation of analytes and formation of renal calculi. Current studies have demonstrated particularities of the excretion of urinary analytes in populations according to their age group. Furthermore, we observed that the uric acid analyte plays a very important role in the formation of kidney stones. Thus, our research proposed to evaluate uric acid concentrations in 24-hour urine samples from children and adolescents in order to bring to light insights on the determination of more consistent reference values. Methodology: In this cross-sectional analytical study, 25 24-hour urine samples were collected from children and adolescents, without comorbidities, to establish reference values ​​in the age group between 4 to 11 years and 12 to 18 years, respectively. Results: The results obtained do not indicate a statistically significant difference in the sex and volume parameters of the total population. However, when observed separately, the adolescents showed a high concentration of uric acid. Our proposal directs the use of 109 and 321.8 mg/24h percentile intervals for the pediatric population. Conclusion: This study proposed insights on reference values ​​for populations with the age groups mentioned above, however, we emphasize the need for more research on this topic and possible adequacy of this study to the requirements stipulated by Clinical and Laboratory Standards.